2014
DOI: 10.18052/www.scipress.com/ilcpa.35.1
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Solar Flares Turn out to Form a Coronal Mass Ejections Events due to the Characterization of Solar Radio Burst Type II and III

Abstract: The solar flare and Coronal Mass Ejections (CMEs) are well known as one of the most massive eruptions which potentially create major disturbances in the interplanetary medium and initiate severe magnetic storms when they collide with the Earth's magnetosphere. However, how far the solar flare can contribute to the formation of the CMEs is still not easy to be understood. These phenomena are associated with II and III burst it also divided by sub-type of burst depending on the physical characteristics and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 185 publications
(252 reference statements)
0
12
0
Order By: Relevance
“…Radio telescopes with antenna systems allow determination of the direction of the source of the solar burst radiation. The main detector, Compound Astronomical Low-frequency, Low-cost Instrument for Spectroscopy Transportable Observatories (CALLIISTO) system is used in obtaining a dynamic spectrum of solar radio burst data [12,13]. At our site, we have constructed the Log Periodic Dipole Antenna (LPDA) and this system was mounted on the top of the rooftop of National Space Centre (ANGKASA) building at Sg.…”
Section: Experimental Setup and Observationmentioning
confidence: 99%
“…Radio telescopes with antenna systems allow determination of the direction of the source of the solar burst radiation. The main detector, Compound Astronomical Low-frequency, Low-cost Instrument for Spectroscopy Transportable Observatories (CALLIISTO) system is used in obtaining a dynamic spectrum of solar radio burst data [12,13]. At our site, we have constructed the Log Periodic Dipole Antenna (LPDA) and this system was mounted on the top of the rooftop of National Space Centre (ANGKASA) building at Sg.…”
Section: Experimental Setup and Observationmentioning
confidence: 99%
“…The magnetic reconnection changes the topology of the field surrounding the flux rope and assist reduce the magnetic tension force that bind the flux rope to the solar surface, hence enhance acceleration of the expulsion. Detailed analysis of the Sun in radio and x-ray region to understand the distribution of high and low energy [28,29,30,31]. We will highlight the solar flare and solar bursts in both electromagnetic radiation.…”
Section: Introductionmentioning
confidence: 98%
“…The factor of this burst is still controversial until now. Previous studies have shown that this burst are produced by CME-driven shock [4,5]. However, there is an evidence and it is believed that the that the metric radio bursts stem from coronal shock waves driven by flares as blast waves Cane and Reames [6].…”
Section: Introductionmentioning
confidence: 99%